2017
DOI: 10.1038/srep46360
|View full text |Cite
|
Sign up to set email alerts
|

Origin of high strength, low modulus superelasticity in nanowire-shape memory alloy composites

Abstract: An open question is the underlying mechanisms for a recent discovered nanocomposite, which composed of shape memory alloy (SMA) matrix with embedded metallic nanowires (NWs), demonstrating novel mechanical properties, such as large quasi-linear elastic strain, low Young’s modulus and high yield strength. We use finite element simulations to investigate the interplay between the superelasticity of SMA matrix and the elastic-plastic deformation of embedded NWs. Our results show that stress transfer plays a domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…According Shahinpoor and Schneider 32 , there are three types of superelastic behavior in SMA work-hardened: superelasticity, linear superelasticity (when martensite is cold worked by about 10%), and nonlinear superelasticity (for which transformation occurs with strain at practically constant stress, presenting narrow hysteresis and small residual strain). Interestingly, the Ni-Ti SMA helical springs manufactured by ICC exhibit a quasi-linear superelasticity, recovering almost all the imposed strains, with narrow stress hysteresis, which is similar to the results of other previous studies 33,34 . Probably, this behavior results from the interaction between the nucleation of martensite in the Ni-Ti matrix phase (austenite) and residual stresses in precipitates during martensitic transformation 35,36 .…”
Section: Tensile Testssupporting
confidence: 89%
“…According Shahinpoor and Schneider 32 , there are three types of superelastic behavior in SMA work-hardened: superelasticity, linear superelasticity (when martensite is cold worked by about 10%), and nonlinear superelasticity (for which transformation occurs with strain at practically constant stress, presenting narrow hysteresis and small residual strain). Interestingly, the Ni-Ti SMA helical springs manufactured by ICC exhibit a quasi-linear superelasticity, recovering almost all the imposed strains, with narrow stress hysteresis, which is similar to the results of other previous studies 33,34 . Probably, this behavior results from the interaction between the nucleation of martensite in the Ni-Ti matrix phase (austenite) and residual stresses in precipitates during martensitic transformation 35,36 .…”
Section: Tensile Testssupporting
confidence: 89%
“…With a planar view (Figure 7(A)), the bright areas in Figure 7 [61] It was reported that the interaction between the nucleation of martensite in the TiNi matrix and the residual stress in Nb precipitates can induce spatially inhomogeneous initiation and propagation of martensite, causing continuous phase transformation resulting in the quasi-linear superelasticity. [62] In this picture, during the interaction the precipitates would bear the overall load in elastic deformation giving rise to the narrow hysteresis and the TiNi matrix behaves as load transfer increases with rising residual stress. [62][63][64][65][66] A criterion based on the large aspect ratio and the volume fraction of precipitates, and applied pre-strain is proposed to achieve the quasi-linear superelasticity in general.…”
Section: Resultsmentioning
confidence: 99%
“…[62] In this picture, during the interaction the precipitates would bear the overall load in elastic deformation giving rise to the narrow hysteresis and the TiNi matrix behaves as load transfer increases with rising residual stress. [62][63][64][65][66] A criterion based on the large aspect ratio and the volume fraction of precipitates, and applied pre-strain is proposed to achieve the quasi-linear superelasticity in general. [62] We believe a similar interaction is taking place here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). The motivation for the choice of such a nanostructure is the advancements in fabrication techniques of composites and their various associated phenomena [41][42] [43]. The Ti-Nb nanocomposite has four microscopic features related to the macroscopic mechanical properties, namely the Nb concentration (CNb) of the matrix (MNb) and nanofillers (FNb), volume fraction of nanofillers (VF), and number of nanofillers (NF).…”
Section: Model and Proceduresmentioning
confidence: 99%